Sobre característica de Euler, links e conjuntos semi-algébricos - Oliveira, Atila Andrade de (2020)
Our goal on this work is to show a proof of Sullivan’s Theorem, who say that Euler characteristic of link on an algebraic set at any point is even. On the process we will study semi-algebraic geometry, algebraic geometry, algebra and topology and introduce a notion that extends the definition of Euler characteristic to semi-algebraic sets, so we will define Euler sets and culminate that every algebraic set is an Euler set.